2012
DOI: 10.1667/rr2950.1
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Metabolomics. 5. Identification of Urinary Biomarkers of Ionizing Radiation Exposure in Nonhuman Primates by Mass Spectrometry-Based Metabolomics

Abstract: Mass spectrometry-based metabolomics has previously demonstrated utility for identifying biomarkers of ionizing radiation exposure in cellular, mouse and rat in vivo radiation models. To provide a valuable link from small laboratory rodents to humans, γ-radiation-induced urinary biomarkers were investigated using a nonhuman primate total-body-irradiation model. Mass spectrometry-based metabolomics approaches were applied to determine whether biomarkers could be identified, as well as the previously discovered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
110
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(120 citation statements)
references
References 33 publications
9
110
1
Order By: Relevance
“…Radiation metabolomics has shown the feasibility of metabolites as biomarkers for ionizing radiation exposure, suggesting that regulation profiles of metabolic processes have indicative potential. Recently, Johnson et al (33) identified several urinary biomarkers in nonhuman primates, among which taurine and xanthine had been identified previously in the mouse (34,35). In fact, responses in genes associated with taurine and xanthine metabolization were regulated in some instances (data not shown).…”
Section: Discussionmentioning
confidence: 95%
“…Radiation metabolomics has shown the feasibility of metabolites as biomarkers for ionizing radiation exposure, suggesting that regulation profiles of metabolic processes have indicative potential. Recently, Johnson et al (33) identified several urinary biomarkers in nonhuman primates, among which taurine and xanthine had been identified previously in the mouse (34,35). In fact, responses in genes associated with taurine and xanthine metabolization were regulated in some instances (data not shown).…”
Section: Discussionmentioning
confidence: 95%
“…7A). Increased urinary excretion of creatine and its catabolite creatinine are biomarkers of whole body irradiation in rats (44), and creatine was identified as a urinary radiation biomarker in a nonhuman primate (11). Notably, baseline creatine levels were much higher in CD47(Ϫ) cells and persisted after irradiation (Fig.…”
Section: Non-mitochondrial Oxygen Consumption Was Minimal Inmentioning
confidence: 94%
“…This was to obtain the actual concentration of each metabolite normalized to the endogenous creatinine concentration. Standard calibration curves were made, and the following MRM transitions were monitored for creatinine Endogenous liver metabolites were quantitated by using an ACQUITY UPLC H-class coupled to a XEVOG2 QTOFMS with Quantof technology (Waters Corp), as recently described (8). Standard calibration curves of 0 to 35 mmol/L of linoleic acid, linolenic acid, adrenic acid, oleic acid, DHA, arachidonic acid, and palmitic acid were made by using authentic standards.…”
Section: Metabolomics Analysismentioning
confidence: 99%